Schooling, Violent Conflict, and Gender in Burundi - Verwimp, Philip; Van Bavel, Jan (Oxford University Press on behalf of the World Bank, 2015)
We investigate the effect of exposure to violent conflict on human capital accumulation in Burundi. We combine a nationwide household survey with secondary sources on the location and timing of the conflict. Only 20 percent of the birth cohorts studied (1971–1986) completed primary education. Depending on the specification, we find that the probability of completing primary schooling for a boy exposed to violent conflict declined by 7 to 17 percentage points compared to a nonexposed boy, with a decline of 11 percentage points in our preferred specification. We also find that exposure to violent conflict reduces the gender gap in schooling, but only for girls from nonpoor households. Forced displacement is one of the channels through which conflict affects schooling. Our results are robust to various specifications and estimation methods.